FOREST TYPES OF THE STAVROPOL UPLAND (ON THE EXAMPLE OF THE DARK FOREST, M. STRIGAMENT) - Anna Evgen’evna Kolsnichenko (Наука. Инновации. Технологии)
The article describes the main stages of the history of the forest typology in Russia, given the landscape map of mount Strigament. The main attention was paid to the forest formations of the study which was conducted by the method of landscape profiling.